Simulasi Pelelehan Freeze Plug Termodifikasi pada Molten Salt Reactor Menggunakan Metode Moving Particle Semi-implicit - Nabiilah, Banafsaj Fatiya; Mustarib, Asril Pramutadi Andi; Yulianto, Yacobus (POSITRON, 2022)
In the Molten Salt Reactor, the freeze plug is one of the components that plays an important role when a reactor accident occurs. In designing the freeze plug, the selection of the constituent material is based on the ability of the material to spread the heat. Therefore, studies on material selection are needed to provide information regarding freeze plug design. The modified freeze plug melting process has been simulated using the Moving Particle Semi-Implicit method. This study aims to observe the behavior of the modified freeze plug melting phenomena and to see the effect of the conductivity value on the melting process. The alloys used around frozen salts with different thermal conductivity are Hastelloy-N, Heynes-242, and ODS Alloy (MA754). The simulation results show that the time required for frozen salt to melt in Hastelloy-N, Heynes-242 variations , and ODS Alloy (MA754) are 12.3 seconds each; 12.7 seconds; and 24.3 seconds. The results obtained explain that freeze plugs with metal alloys that have the highest thermal conductivity require a shorter time to reach the melting point. This shows that the greater the thermal conductivity value, the easier it is to spread heat to the alloy that hits the frozen salt.